Estudo do complexo das doenças respiratórias dos bovinos em confinamento de terminação: fatores de risco, aspectos clínicos e anatomopatológicos - Matheus Ferreira Serafini (2016)
The Bovine Respiratory Disease Complex (BRDC), a respiratory syndrome, so-called when uncertain definitive diagnosis. Cause of large losses in feedlot an injury to the animal welfare. The aim of this study was to identify the major injuries on respiratory tract within the animals that died and it losses to the feedlot. The experiment was conducted in a beef feedlot at Brazilian southeastern, with a carrying of 16.625 beef steers, predominantly zebu, housed in rubble pens. For a period of six months, was monitored the daily life of feedlot with inspection, clinical and necropsy examination of 134 bovines that died, and samples was collected in formalin 10% following by histological processing and analysis to determine the injuries. The macroscope and microscope changes were registered and compared to define the cause of death. From a total of 134 death animals, in 94,8% lesions were found in any system, and 44,1% had alterations in the respiratory tract, 6,7% in the nervous system, the urinary system 5,2% and 0,8% in the digestive system.